Pengaruh penggunaan media pembelajaran daring terhadap kepuasan pada Saat pandemi Covid-19 guru siswa Sekolah Dasar - Yudi Prianto (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research is to determine the effect of online media on teacher satisfaction. The existence of this pandemic has had an impact on all sectors, one of which is education, before the pandemic occurred face-to-face became a medium for learning interactions but now it has switched to an online system (online), this online activity applies to all levels of education. Meanwhile, online learning media has been implemented since the beginning of the pandemic as an alternative in delivering learning material. Of the various types of learning media used during this pandemic, Google Classroom is the main choice chosen by respondents. The research results show that the variable use of online media and learning motivation has a positive value meaning that the better the choice in using online media the teacher will feel satisfied. As for this research method is descriptive quantitative using PLS with data analysis methods including validity testing, reliability testing, multiple linear regression analysis and using the t test. The conclusion of this research states that showing the use of online media has an influence on teacher satisfaction